2001
DOI: 10.1016/s0166-2236(00)01959-7
|View full text |Cite
|
Sign up to set email alerts
|

Restless AMPA receptors: implications for synaptic transmission and plasticity

Abstract: A central assumption in neurobiology holds that changes in the strength of individual synapses underlie changes in behavior. This concept is widely accepted in the case of learning and memory where LTP and LTD are the most compelling cellular models. It is therefore of great interest to understand, on a molecular level, how the brain regulates the strength of neuronal connections. We review a large body of evidence in support of the very straightforward regulation of synaptic strength by changing the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 67 publications
1
46
0
3
Order By: Relevance
“…A large body of experimental evidence now supports this hypothesis (Lüscher et al 2000;Lüscher and Frerking 2001;Malinow and Malenka 2002;Nicoll 2003;Collingridge et al 2004;Malenka and Bear 2004). In fact, AMPARs can be quite mobile and recycle between the cytoplasm and the cell membrane even under baseline conditions within tens of minutes.…”
Section: Expression Mechanismmentioning
confidence: 88%
“…A large body of experimental evidence now supports this hypothesis (Lüscher et al 2000;Lüscher and Frerking 2001;Malinow and Malenka 2002;Nicoll 2003;Collingridge et al 2004;Malenka and Bear 2004). In fact, AMPARs can be quite mobile and recycle between the cytoplasm and the cell membrane even under baseline conditions within tens of minutes.…”
Section: Expression Mechanismmentioning
confidence: 88%
“…This was interpreted as evidence that AMPA receptors were inserted into the postsynaptic membrane after induction of LTP. Since then, a great deal of evidence has been accumulated indicating that AMPA receptor expression on cells is a dynamic process and is controlled by a cycle of exocytosis and endocytosis (351,372). It has also been repeatedly shown in cultured cells that this cycle is modulated by NMDA receptor activation which leads to increased recruitment of AMPA receptors and increased AMPA-mediated miniature EPSPs (324,345,565).…”
Section: Ampa Receptors and Ltpmentioning
confidence: 99%
“…In mammalian systems, changes in glutamate receptor expression have been proposed as a mechanism of memory formation (Lüscher and Frerking 2001;Malinow and Malenka 2002). Rose et al (2003) showed that the AMPA-type glutamate receptor subunit, GLR-1, was required for long-term habituation-glr-1 loss-of-function mutants habituated but did not retain decremented responses.…”
Section: Long-term Memorymentioning
confidence: 99%